Successful regenerative approach with direct pulp capping using mineral trioxide aggregate after pulpal injury 2 years follow-up: case report - Andriani, Poppi; Dwisaptarini, Ade Prijanti; Fibryanto, Eko; Mohd Noh, Nur Zety (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
Introduction: A complete excavation of dental caries can accidentally expose the pulp. Pulp exposure should be sealed immediately to maintain pulp vitality and heal after injury, called direct pulp capping. Direct pulp capping can stimulate the formation of dentinal bridgess to maintain pulp vitality after injury using biomaterial agents The objective of this case report is to demonstrate the efficacy of regenerative endodontic approach, specifically direct pulp-capping therapy using mineral trioxide aggregate, in treating the injury with a six-month follow up. Case report: A 19-yearold female complained of slight discomfort while drinking cold water on her right second incisor. Clinical examination revealed proximal dentin caries. Vitality and percussion tests were negative. Radiograph examination showed a radiolucent area on the mesial proximal part that affected both enamel and dentin. The tooth was diagnosed with reversible pulpitis. The area was isolated with a rubber dam. Dentin caries was removed using the rotary instrument. In the process, the pulp cavity was exposed iatrogenically at one site with minor bleeding, so direct pulp capping was applied to maintain pulp vitality. The cavity was disinfected with chlorhexidine 2%. Mineral Trioxide Aggregate (MTA) was selected as the material for direct pulp capping. Initially, it was administered to the exposed pulp, succeeded by the application of glass ionomer cement and temporary restoration. Two years follow-up, positive vitality and negative percussion test results were observed. X-rays showed the formation of hard tissue, and there were no pathological findings in the apical on tooth #12. Conclusion: When pulp is exposed due to deep caries, endodontic regenerative methods involving biomaterial agents can be employed. MTA has the capacity to encourage the formation of dentinal bridges and promote pulpal regeneration following an injury.